2021
DOI: 10.15252/embj.2021107958
|View full text |Cite
|
Sign up to set email alerts
|

Ice2 promotes ER membrane biogenesis in yeast by inhibiting the conserved lipin phosphatase complex

Abstract: Cells dynamically adapt organelle size to current physiological demand. Organelle growth requires membrane biogenesis and therefore needs to be coordinated with lipid metabolism. The endoplasmic reticulum (ER) can undergo massive expansion, but the underlying regulatory mechanisms are largely unclear. Here, we describe a genetic screen for factors involved in ER membrane expansion in budding yeast and identify the ER transmembrane protein Ice2 as a strong hit. We show that Ice2 promotes ER membrane biogenesis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 93 publications
2
26
0
Order By: Relevance
“…We next wondered if the DG kinase Dgk1, which catalyses the reverse reaction to lipin by phosphorylating DG to produce PA, contributed to the decrease in DG levels at the INM during mitosis of S. pombe . Dgk1 was previously identified in S. cerevisiae (Han et al, 2008), and was recently shown to display a mild under-expanded ER phenotype (Papagiannidis et al, 2021), hinting at its role in controlling ER growth. The S. pombe ortholog is encoded by the ptp4/dgk1 gene (SPBC3D6.05) (referred to as Dgk1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next wondered if the DG kinase Dgk1, which catalyses the reverse reaction to lipin by phosphorylating DG to produce PA, contributed to the decrease in DG levels at the INM during mitosis of S. pombe . Dgk1 was previously identified in S. cerevisiae (Han et al, 2008), and was recently shown to display a mild under-expanded ER phenotype (Papagiannidis et al, 2021), hinting at its role in controlling ER growth. The S. pombe ortholog is encoded by the ptp4/dgk1 gene (SPBC3D6.05) (referred to as Dgk1).…”
Section: Resultsmentioning
confidence: 99%
“…3A, B and (Makarova et al, 2016)). It also does not increase in the budding yeast spo7 Δ and nem1 Δ mutants despite the block to lipin activity (Papagiannidis et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…5,15 Defect in PC production disturbs membrane development and altered intracellular membrane trafficking. 5,22,62,63,73,74 In gcr1Δ cells there was perturbation in the intracellular membrane arrangement (Figure S4) and this could be attributed to the reduced PC content that was restored with GCR1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Lipidomics analyses were performed as described in Papagiannidis et al (2021) . Aliquots corresponding to 1500-2000 pmol total lipid were subjected to acidic Bligh and Dyer extractions performed in the presence of internal lipid standards from a master mix containing 40 pmol d 7 -PC mix (15:0/18:1-d7, Avanti Polar Lipids), 25 pmol PI (17:0/20:4, Avanti Polar Lipids), 25 pmol PE and 15 pmol PS (14:1/14:1, 20:1/20:1, 22:1/22:1, semi-synthesized as described in Özbalci et al, 2013), 20 pmol PA (PA 17:0/20:4, Avanti Polar Lipids) 5 pmol PG (14:1/14:1, 20:1/20:1, 22:1/22:1, semi-synthesized as described in Ozbalci et al (2013) , 25 pmol CL 57:4 (14:1/14:1/14:1/15:1, Avanti Polar Lipids) and 25 pmol MLCL (16:0/16:0/16:0, Echelon).…”
Section: Lipid Analysismentioning
confidence: 99%